Constraints on Innovative Teaching in British Universities: An American Perspective - David M. Schultz (Park University, 2019)
Effective teaching is often difficult to achieve because institutional frameworks and inertia - unique to the British educational system - inhibit teachers from being innovative. These challenges to more innovative teaching are the relatively short length of time to a degree, and the heavy institutional oversight of degree programs and individual courses. Also, the tradition of lack of regular feedback and failures in the supervision and marking of undergraduate dissertations also lead to a less-than-ideal educational experience. Fortunately, some of these challenges can be overcome and provide a better learning experience for students.